Physics teachers' attitudes towards using Polya`s strategy for solving physics problems at Post Basic Education in Sultanate of Oman - Al- Badri, Ahmed Humaid; Al- Jabri, Hamed Said Ali (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify Physics teachers' attitudes towards using Polya`s strategy for solving physics problems at Post Basic Education stage. To achieve the objectives of the study, a direction measurement was built to identify the degree of physics teachers' attitudes towards using Polya`s strategy. The measurement consisted in its final form of (34) statements. The sincerity of arbitrators of study tool was calculated and the correlation coefficients of the measurement statements was (0.567- 0.802). The stability of scales was also calculated by applying it on an exploratory sample and the reliability coefficient was (0.87) which is a high index of relevance to achieve objectives of the study. A descriptive approach was used to achieve the objectives of the study and the study population consisted of all physics teachers at Post Basic Education of Al Batinah North and Muscat Governorates in the academic year 2016/2017.A representative sample was chosen in a random way; the study sample was (41) male and female physics teachers of Post BE stage and the study tool was applied on them. The study results indicated that the average sample study of physics teachers' attitudes towards Polia strategy on a full scale was (3.76), which is a high degree level according to the standard of correcting performance on study tool which is a higher degree than the acceptable level educationally (3.5); that is due to the physics teachers of the importance of Polia strategy in developing skills of solving physics problems for learners.The results of the study indicated also that there were no statistically significant differences in the physics teachers' attitudes towards using Polya`s strategy in solving physics problems in Post BE, according to the variables of gender, scientific qualification and teaching experience. The researchers attribute that to the modernity of this strategy for physics teachers and the presence of a real desire from physics teachers to develop their teaching skills in solving physics problems in grade 11 and 12 (Post Basic EducationThe study recommended the need for paying attention to the development of physics teachers' skills in Polya strategy with its four(4) steps in teaching and solving physics problems at Post BE, and continuing work to raise awareness level and positive attitudes among physics toward Polya strategy and its importance in solving physics problems process.
Keywords: Trends; Physics Teachers; Paulia Strategy; Physical Issues; Post; Basic Education